Influence of Ethylene bis-Stearamide on Crystallization Behaviour of Poly(L-lactide) - Cai, Yan-Hua (Asian Journal of Chemistry, 2013)
The crystallization behaviour of poly(L-lactide) (PLLA)/ethylene bis-stearamide (EBS) composites with different content of EBS has been investigated by differential scanning calorimetry (DSC), polarization optical microscopy (POM) and thermogravimetric analysis. Ethylene bis-stearamide can accelerate the crystallization of PLLA upon the addition of 1 % EBS, the crystallization peak is most obvious and sharp, which indicates the best effect of crystallization at 1 % EBS. Cooling rate affect the process of crystallization of PLLA, with increasing of the cooling rate, the crystallization peak becomes wider and shifts to a lower temperature. Polarization optical microscopy shows that EBS make the spherulite size of PLLA decrease dramatically and the spherulite number become large. And the decomposition temperature of PLLA/EBS is slightly lower than that of neat PLLA.